Oxidative Stress as a Physiological Pain Response in Full-Term Newborns. (4th January 2017) - Perrone, S.; Bellieni, C. V.; Negro, S.; Longini, M.; Santacroce, A.; Tataranno, M. L.; Bazzini, F.; Belvisi, E.; Picardi, A.; Proietti, F.; Iantorno, L.; Buonocore, G.
Abstract : This research paper aims to investigate if oxidative stress biomarkers increase after a painful procedure in term newborns and if nonpharmacological approaches, or sex, influence pain degree, and the subsequent OS. 83 healthy term newborns were enrolled to receive 10% oral glucose or sensorial saturation (SS) for analgesia during heel prick (HP). The ABC scale was used to score the pain. Advanced oxidation protein products (AOPP) and total hydroperoxides (TH) as biomarkers of OS were measured at the beginning (early-sample) and at the end (late-sample) of HP. The early-sample/late-sample ratio for AOPP and TH was used to evaluate the increase in OS biomarkers after HP. Higher levels of both AOPP and TH ratio were observed in high degree pain (4–6) compared with low degree pain score (0–3) (AOPP: p = 0.049 ; TH: p = 0.001 ). Newborns receiving SS showed a significantly lower pain score (p = 0.000 ) and AOPP ratio levels (p = 0.021 ) than those without. Males showed higher TH levels at the end of HP (p = 0.005 ) compared to females. The current study demonstrates that a relationship between pain degree and OS exists in healthy full-term newborns. The amount of OS is gender related, being higher in males. SS reduces pain score together with pain-related OS in the newborns.